Effect of organic acid pre-treatment on polyphenol oxidase induced browning and sensory quality of frozen yam chips - Naomi A. Eshun; Winfred-Peck Dorleku; Firibu K. Saalia; Marikis N. Alvarez; Alberta N.A. Aryee (Applied Food Research, 2022)
Yam Dioscorea spp suffers about 30% postharvest losses annually. Processing into convenience products such as yam chips prolong shelf life although the action of enzymes including polyphenol oxidase (PPO) and peroxidase (POD) may affect the quality if not precluded. Pre-treatment of cut yam with pH modifiers and antioxidants before storage could reduce enzymatic browning. In this study we investigated the effectiveness of ascorbic acid, citric acid and lime juice treatment and 5 weeks (w) of frozen storage in reducing browning in yam chips without affecting sensory quality. PPO and POD activity of freshly prepared yam chips pre-treated with citric acid, ascorbic acid or lime juice and stored frozen at -18 °C for 5 weeks was determined. The yam chips were fried and the moisture, oil content and colour determined. Consumer acceptability sensory evaluation was conducted for the week 0 and 5 of stored samples. POD activity was significantly reduced (50%) by treatment with citric acid after five-weeks of frozen storage while treatment with ascorbic acid and lime juice had no effect on the enzyme activity. There was no significant difference in lightness between the different treatments although treated samples differed significantly from the untreated. Moisture content of all samples were lower after storage while oil content of the various treatments was significantly different. Notwithstanding these differences, consumer acceptability was not different between the various treatment and storage periods. Pre-treated frozen yam chips have a good consumer acceptance and potential for commercial application. Developing this product will add value to yams and reduce huge postharvest losses.